2022
DOI: 10.3389/fphar.2022.876183
|View full text |Cite
|
Sign up to set email alerts
|

An Overview of the Evidence and Mechanism of Drug–Herb Interactions Between Propolis and Pharmaceutical Drugs

Abstract: With the growing interest in the medicinal use of propolis, numerous studies have reported significant interactions between propolis extract and pharmaceutical drugs which may result in great clinical benefits or risks. The present study aims to review the drug–herb interactions of the full-spectrum propolis extract and main pharmaceutical drugs from the pharmacodynamic and pharmacokinetic aspects and elucidate the underlying pharmacological mechanisms. A literature search was conducted between June 2021 and F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 141 publications
1
14
0
Order By: Relevance
“…Some herbal extracts or components enhanced the antibacterial activity of antimicrobial agents against sensitive and multidrug-resistant microorganisms when combined with antibiotics. 176,177 The synergistic or additive action was possibly related to multiple compounds in herbal extracts jointly acting on multiple sites and targets of bacteria by damaging the bacteria cell wall and membrane, 178 facilitating drug entry, inhibiting drug efflux pumps 179 and enzymes that invalidate chemical antimicrobial agents (such as penicillinase and β-lactamase). Meanwhile, some research technologies, such as new omics technologies and network pharmacology, become an asset for finding the most effective combinations among antimicrobial herbs or in combination with currently available synthetic antibiotics.…”
Section: Discussionmentioning
confidence: 99%
“…Some herbal extracts or components enhanced the antibacterial activity of antimicrobial agents against sensitive and multidrug-resistant microorganisms when combined with antibiotics. 176,177 The synergistic or additive action was possibly related to multiple compounds in herbal extracts jointly acting on multiple sites and targets of bacteria by damaging the bacteria cell wall and membrane, 178 facilitating drug entry, inhibiting drug efflux pumps 179 and enzymes that invalidate chemical antimicrobial agents (such as penicillinase and β-lactamase). Meanwhile, some research technologies, such as new omics technologies and network pharmacology, become an asset for finding the most effective combinations among antimicrobial herbs or in combination with currently available synthetic antibiotics.…”
Section: Discussionmentioning
confidence: 99%
“… 22 HDIs can occur on both a pharmacodynamic and pharmacokinetic basis. Pharmacokinetic interaction involves the modulation of absorption, distribution, metabolism, and excretion of drugs by affecting drug transporters and CYP450 enzymes, 23 and the majority of potential HDIs occur on a pharmacokinetic level. 21 …”
Section: Resultsmentioning
confidence: 99%
“…pharmacodynamic and pharmacokinetic basis. Pharmacokinetic interaction involves the modulation of absorption, distribution, metabolism, and excretion of drugs by affecting drug transporters and CYP450 enzymes, 23 and the majority of potential HDIs occur on a pharmacokinetic level. 21 The results of our previous HDI study showed that Danzhi Xiaoyao pills could reduce the plasma exposure of venlafaxine and increase the plasma concentration of its metabolite ODV (the major active metabolite of venlafaxine) and NDV (the minor metabolite of venlafaxine) in beagle dogs.…”
mentioning
confidence: 99%
“…The first widely cited study about synergism between propolis and antibiotics involved European propolis and several antibiotics, working in synergy against S. aureus [ 156 ]. An extensive list has been published, involving tests with a diversity of antibiotics, microorganisms, and propolis from distinct localities [ 157 ]. The authors commented that most studies have enhanced the effects promoted by propolis extracts by comparing zones of inhibition or MIC values rather than determining the FIC index, a parameter that indicates synergy if the result is ≤0.5.…”
Section: Synergy With Other Antimicrobial Substancesmentioning
confidence: 99%